1985
DOI: 10.1002/micr.1920060308
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for perfusion and storage of heterotopic heart transplants in mice

Abstract: Organ pretreatment prior to transplantation has assumed increasing importance. We studied the ability to preserve and perfuse hearts in well-defined genetic mouse models, prior to heterotopic engraftment. Hearts were manually perfused through the aortic root and stored in a variety of cold solutions or were perfused using a continuous perfusion pump. Different electrolyte solutions, mouse strains, perfusion, and storage times as well as perfusion volumes were studied. Treated hearts were than transplanted hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…This was not due to the systemic lymphocyte depletion as the numbers of spleen T lymphocytes were comparable in control and AER-271 injected mice on day 3 and at the end of the treatment (16.5 ± 0.8 × 10 6 vs 14.0 ± 1.0 × 10 6 for CD4 T cells and 7.3 ± 0.3 × 10 6 vs 7.8 ± 0.5 × 10 6 for CD8 T cells). Similar improved graft survival and decreased priming of donor-reactive T cells were observed for heart allografts subjected to 8 h CIS in Ringer’s lactate, a solution commonly used in rodent organ transplantation (Figure 2C–D) (24, 25). Despite impaired T cell alloimmunity, recipients treated with AER-271 developed donor-reactive IgG alloantibodies (Figure 2E).…”
Section: Resultssupporting
confidence: 69%
“…This was not due to the systemic lymphocyte depletion as the numbers of spleen T lymphocytes were comparable in control and AER-271 injected mice on day 3 and at the end of the treatment (16.5 ± 0.8 × 10 6 vs 14.0 ± 1.0 × 10 6 for CD4 T cells and 7.3 ± 0.3 × 10 6 vs 7.8 ± 0.5 × 10 6 for CD8 T cells). Similar improved graft survival and decreased priming of donor-reactive T cells were observed for heart allografts subjected to 8 h CIS in Ringer’s lactate, a solution commonly used in rodent organ transplantation (Figure 2C–D) (24, 25). Despite impaired T cell alloimmunity, recipients treated with AER-271 developed donor-reactive IgG alloantibodies (Figure 2E).…”
Section: Resultssupporting
confidence: 69%
“…Graft function was evaluated daily accordingly to the heart beat score evaluation as reported in [20], scoring system: 0: no organ function, 1: fibrillation, only visible through magnification, 2: poor or partial organ function, 3: impairment in frequency or intensity of heart beating, 4: physiological organ function.…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged storage of donor hearts in a cold solution has been shown to cause mechanical dysfunction. 25 The results of our acute experiment using antimyosin clearly indicated that storage of donor hearts in a cold solution causes significant ischemic myocyte necrosis. Grafts with an isehemic time of more than 90 minutes showed significantly increased antimyosin uptake in comparison with grafts with an ischemia time of less than 60 minutes.…”
Section: Discussionmentioning
confidence: 79%